Боевой путь генерал-адъютанта М. 3. Аргутинского-Долгорукого - Сергей Минасян (ՀՀ ԳԱԱ հրատ.)
Ռուսական Կովկասյան բանակի հայ զորավարների փայլուն համաստեղության մեջ առանձնանում էր Մ. Զ. Արղության-Երկայնաբազուկը(Долгорукий, 1797-1855)։ Նա սերում էր Արղությանների հայտնի իշխանական տոհմից։ Նա հայ զորավարներից առաջինն էր, որն արժանացավ ռուսական բանակի գեներալ-ադյուտանտի բարձր կոչմանը: Within the glorious constellation of the Russian Caucasian Army's Armenian commanders M.Z. Arghutyan - Dolgoruky (1797-1855) was an exceptional case. He originated from the renowned noble family of the Arghutyans.He was the first among the Armenian military who was rewarded with the high rank of Russian Army - General-Adjutant.
Keywords: History; Biography; Auxiliary Sciences of History; Military Science; D History